Pengaruh Keterampilan Komunikasi Guru Pendidikan Agama Kristen terhadap Efektivitas Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP N 2 Balige Tahun Pembelajaran 2023/2024 - Beni Fernando Sihotang; Frainskoy Rio Naibaho; Ordekoria Saragih; Hasudungan Simatupang; Senida Harefa (Jurnal Magistra, 2024)
The aim of this research is to determine the positive and significant influence of Religious Education Teachers' Communication Skills on the Effectiveness of Students' Learning in Religious Education and Character Subjects in Class VIII of SMP Negeri 2 Balige for the 2023/2024 Academic Year. The method used in this research is an inferential quantitative method. The population was all students in class VIII of SMP Negeri 2 Balige who were Protestant Christians, totaling 227 people, and the research sample was determined to be 56 people, namely 25% of the total population. Data was collected using a positive closed questionnaire with 44 items. The results of the data analysis show that there is a positive and significant influence on the communication skills of PAK teachers on the effectiveness of students' learning in the PAK and Character subjects for Class VIII at SMP Negeri 2 Balige for the 2023/2024 academic year, proven through the following data analysis: 1) Requirement test analysis: a) a positive relationship test obtained a value of rxy = 0.520 > ttable(a=0.05,n=56) = 0.226, thus it is known that there is a positive relationship between variable X and variable Y. b) A significant relationship test was obtained tcount= 4.479 > ttabel(a=0,05,dk=n-2=54))= 2.000, thus there is a significant relationship between variable X and variable Y. 2) Test the effect: a) Test the regression equation, obtain the regression equation Y ̂="21.41"+0.48X. b) Regression coefficient of determination test (r2) = 27.1%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable =(a=0.05, dk numerator k=29, dk denominator=n-2=56-2=54) namely 20.01 > 1.39. Thus it can be concluded that Ha is accepted and H0 is rejected.